Increased Circulating Exosomal miRNA-223 Is Associated with Acute Ischemic Stroke - Chen, Yajing; Song, Yaying; Huang, Jun; Qu, Meijie; Zhang, Yu; Geng, Jieli; Zhang, Zhijun; Liu, Jianrong; Yang, Guo-Yuan (Frontiers in Neurology, 2017)
Recent studies have demonstrated that exosomal microRNAs (miRNAs) are novel biomarkers and therapeutic targets for various diseases including vascular disease. However, specific exosomal miRNAs expression in stroke patients has not been reported yet. Here we explored whether circulating exosomal miRNAs can serve as potential biomarkers for the diagnosis of acute ischemic stroke and discussed the potential for clinical application. Blood samples were collected from acute ischemic stroke patients within the first 72 hours (n=50). Circulating exosomes were exacted by Exoquick exosome isolation kit and characterized by transmission electron microscopy (TEM). Western Blot was performed to assess the expression of exosomal protein makers. Exosomal microRNA-223 (miR-223) was detected by RT-PCR assay. The relationship between the expression levels of miR-223 and national institutes of health stroke scale (NIHSS) scores, brain infarct volume and neurological outcomes were analyzed. Circulating exosomes were isolated and the size of vesicles ranged between 30 and 100 nm. The identification of exosomes was further confirmed by the detection of specific exosomal protein markers CD9, CD63 and Tsg101. Exosomal miR-223 in acute ischemic stroke patients was significantly up-regulated compared to control group (p<0.001). Exosomal miR-223 level was positively correlated with NIHSS scores (r=0.31, p=0.03). Exosomal miR-223 expression in stroke patients with poor outcomes was higher than those with good outcomes (p<0.05). Increased exosomal miR-223 was associated with acute ischemic stroke occurrence, stroke severity and short term outcomes. Future studies with large sample are needed to assess the clinical application of exosomal miR-223 as a novel biomarker for ischemic stroke diagnosis.